PENGEMBANGAN MEDIA PEMBELAJARAN E-KOMIK PADA MATERI GAYA KELAS IV DI SEKOLAH DASAR - Alda Indah Syafitri; Nana Hendracipta; Encep Andriana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop an e-comic learning medium for fourth-grade elementary school students on the topic of style and to determine its feasibility. The background of this research is the low interest of students in learning abstract science and science subjects. Therefore, an engaging and easy-to-understand learning medium is needed. The R&D (Research and Development) method was used in this study, and the procedure applied the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation. The trial subjects were 22 fourth-grade students at SDI Baitul Salam. Data were obtained through a validation questionnaire conducted by material experts and media experts. The media expert validation results obtained a percentage of 80.5%, categorized as "Feasible," while the material validation results obtained a percentage of 92%, categorized as "Very Feasible." Based on the results, the e-comic learning medium was declared feasible and effective for use as an alternative medium in science and science subjects, particularly on style subjects in fourth-grade elementary school.